A Rare Case of Acute Promyelocytic Leukemia with Morphologic Dysplasia and Unique Molecular Characteristics - Kim, Ye Hyun; Park, Joo-Heon; Lim, Ha Jin; Choi, Yong Jun; Choi, Hyun-Jung; Choi, Hyun-Woo; Kee, Seung-Jung; Kim, Soo Hyun; Shin, Jong Hee; Shin, Myung-Geun (Laboratory Medicine Online, 2024)
Acute promyelocytic leukemia (APL) is a distinct acute myeloid leukemia characterized by abnormal promyelocyte predominance. Typical APL cases rarely present dysplastic changes and disease progression of de novo myelodysplastic syndrome to APL is also very uncommon, which makes APL suspicion difficult in cases with dysplasia. Here, we report a unique case of APL featuring morphologic dysplasia. As for our patient, there were several additional unusual findings: the initial bone marrow examination did not reveal an increase in promyelocytes, but rather showed a modest increase in myeloblasts with normal coagulation profiles and a normal karyotype. Moreover, decrease of initially detected ETV6 mutations as well as new FLT3 mutations were observed on repeated targeted sequencing. The possibility of APL should not be overlooked even at the slightest increase of promyelocytes, and early diagnostic tests for fusion transcripts should be considered. KCI Citation Count: 0